American dream, American nightmare : fiction since 1960 - Hume, Kathryn, 1945- (Urbana : University of Illinois Press, 2000)
"Kathryn Hume explores how estrangement from America has shaped the fiction of a literary generation, which she calls the Generation of the Lost Dream." "In breaking down the divisions among standard categories of race, religion, ethnicity, and gender, Hume identifies shared core concerns, values, and techniques among seemingly disparate and unconnected writers including T. Coraghessan Boyle, Ralph Ellison, Russell Banks, Gloria Naylor, Tim O'Brien, Maxine Hong Kingston, Walker Percy, N. Scott Momaday, John Updike, Toni Morrison, William Kennedy, Julia Alvarez, Thomas Pynchon, Leslie Marmon Silko, and Don DeLillo." "Hume explores fictional treatments of the slippage in the immigrant experience between America's promise and its reality. She exposes the political link between contemporary stories of lost innocence and liberalism's inadequacies. She also invites us to look at the literary challenge to scientific materialism in various searches for a spiritual dimension in life."--Jacket.
1. The Shocks of Transplantation -- 2. Mythical Innocence -- 3. Yearning for Lost Civilization -- 4. Seeking Spiritual Reality -- 5. The Fragility of Democracy -- 6. Demonic Visions -- 7. Liberating the Land of Freedom -- 8. Small Is Beautiful -- 9. The Failure of the Dream in Fiction.
Includes bibliographical references (pages 319-345) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: American fiction -- 20th century -- History and criticism; Failure (Psychology) in literature; Literature and society -- United States -- History -- 20th century; Psychological fiction, American -- History and criticism; National characteristics, American, in literature; Loss (Psychology) in literature; Disappointment in literature; Economics in literature; Success in literature; Roman américain -- 20e siècle -- Histoire et critique; Échec dans la littérature.; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; Roman psychologique américain -- Histoire et critique; Américains dans la littérature.; Perte (Psychologie) dans la littérature.; Déception dans la littérature.; Économie politique dans la littérature.; Succès dans la littérature.; LITERARY CRITICISM / General; American fiction; Disappointment in literature; Economics in literature; Failure (Psychology) in literature; Literature and society; Loss (Psychology) in literature; National characteristics, American, in literature; Psychological fiction, American; Success in literature; United States; Roman; USA; Fictie; Amerikaans; Geschichte 1960-2000.; Geschichte (1960-1990); 1900-1999; Criticism, interpretation, etc; History